Description of The Implementation of Character Values In The Project For Strengthening The Pancasila Student Profile (P5) Sustainable Lifestyle Theme - Safitri, Dian Eka; Hairida, Hairida; Mayasari, Eni (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This research aims to describe the implementation of character values in the Project for Strengthening the Profile of Pancasila Students (P5) at SMA Negeri 8 Pontianak. The method applied in this research is descriptive qualitative. Data was collected through observation, interviews and documentation studies. The focus of this research is on class X students at SMA Negeri 8 Pontianak. P5 is one of the innovations in the Merdeka Curriculum which aims to instill Pancasila values and develop student character through project-based learning. The research results show that character values such as independence, cooperation, responsibility and creativity have been successfully implemented in P5 activities. Through this activity, students are given the opportunity to make their own decisions, which encourages the development of their independence. Additionally, students learn to collaborate in groups, which strengthens students' social and collaborative skills. Students also develop a sense of responsibility by ensuring that individual and group assignments are completed well and on time. Additionally, P5 activities provide students with space to think creatively and find innovative solutions to the challenges they face, which enriches their critical thinking and problem-solving skills. The strategies implemented by teachers in P5 activities include presenting systematic project modules, strengthening a supportive school culture, and increasing the capacity of educators. This research shows that P5 is very supportive in shaping student character in accordance with the Pancasila Student Profile, as well as providing insight for other schools in implementing similar programs to strengthen character education.